Dampak Game Online pada Peserta Didik: Studi Kasus Kelas IV SD Negeri Bojong 02 Kecamatan Jatibarang Kabupaten Brebes - Maulia Mitha Utomo; Yasin; Didik Tri Setiyoko (Attractive : Innovative Education Journal, 2024)
Online games are games that can be accessed by many players where the machines used by the players are connected by a network. Generally, the network used to play is the Internet. The rise of online games has caused players to become addicted to these games. The addiction phase of playing games is a situation where it is very difficult for a player to escape from the game, so that the learning activities of children and teenagers are disrupted. This research aims to describe the influence of playing online games on learning activities in grade IV school-aged children at SDN Bojong 02, Jatibarang District, Brebes Regency. The method in this research uses a qualitative approach with a sample of 12 people. It can be seen that the learning activities of children who do not play online games are better than children whose activities play online games because it can be seen from the daily activities they do at home and at school that it can influence their learning activities so that they need supervision and control from parents and teachers to be able to provide direction. or understanding the dangers of online game addiction so that they can be responsible as students whose job is only to study, not to play online games. The influence of playing online games on learning activities in grade IV (Four) school age children at SDN Bojong 02, Jatibarang District, Brebes Regency. For further researchers, it can be developed into research on the influence of playing online games on changes in sleep patterns in teenagers